HUBUNGAN USIA PERTAMAKALI MELAKUKAN HUBUNGAN SEKS DENGAN KEJADIAN KANKER SERVIKS DI RUMAH SAKIT PUSAT HAJI ADAM MALIK MEDAN - , Syahrial Umri ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Age at the initiation sexual intercourse was closely related to the incidence of cervical cancer. Having sexual intercourse at young age became a risk factor of the cervical cancer occurrence because of metaplasia caused by ectopy. The increased risk was probably due to the influence of steroid hormones on HPV infection and the host immune response against the HPV during the preteens and teens. Objective: To determine the relationship between age at the initiation sexual intercourse with the risk of cervical cancer. Methods: This study used a design of hospital - based case control study. The case samples were cervical cancer patients in Haji Adam Malik General Hospital Center in 2009-2013, while the control samples were patients without cervical cancer matched on age. The research instruments are questionnaire about the respondent's identity, medical history, history of marriage, contraceptive use, smoking and genital hygiene. Total of sample was 134 people, namely 67 cases and 67 controls. Data analysis used the McNemar test and conditional logistic regression with a significance level of p < 0.05 and 95% of confidence intervals. Results: The results of bivariable analysis showed a significant association between age at the initiation sexual intercourse < 20 years with cervical cancer OR = 6(95% CI:1,75-31,79). On the results of the multivariable analysis after controlling by parity and level of education OR were 2,1 (95% CI: 0, 55 â 8,39) Conclusion: Directly there was significant relationship between age at the initiation sexual intercourse with cervical cancer, but when the control is done by inserting parity and level of education, age at the initiation sexual intercourse is become non-significant against cervical cancer.